Clinical scale to assess of bronchial obstruction severity at preschoolers - E. M. Kamaltynova; I. A. Deev; O. S. Fedorova; N. V. Nikolaeva; M. I. Polevshchikova (Бюллетень сибирской медицины, 2018)
The severity of the disease is the main factor for further treatment. Bronchoobstructive syndrome of children is widespread. Early detection of the disease severity and correct treatment eliminate the clinical manifestation of the syndrome and improve the quality of patients life. Criteria of severity, as a rule, serve a certain set of clinical and paraclinical parameters used for different nosological forms. In particular, the decrease in parameters of the function of external respiration is the “gold standard” for assessing the severity. Lung function tests for preschoolers are limited. Clinical respiratory scales may be useful in the evaluation of preschooler. Alternative assessment respiratory function is sometimes used as clinical scale. Numerous studies devoted to the objective assessment of bronchial obstruction syndrome severity. A scientific literature review is dedicated to the analysis to the assessment of the bronchoobstructive syndrome severity degree and the effectiveness of therapy at preschool-aged children.